Resource sharing today a practical guide to interlibrary loan, consortial circulation, and global cooperation - Nyquist, Corinne (Rowman & Littlefield, 2014)
"Budget constraints challenge collection development in unprecedented ways. Collection development has increasingly become a cooperative effort among libraries in geographic proximity. When their own library doesn't have certain books or journals, users turn to interlibrary loan to obtain the resources they need. However, many library science degree programs don't cover interlibrary loan. Resource Sharing Today is a practical guide to resource sharing starting with the library across town and ending with libraries on the other side of the globe. Chapters cover everything from the ALA's interlibrary loan form to successful innovations such as Virginia Tech's ILLiad to New York's IDS (Information Delivery Service). Appendices include regional, state, national, and international ILL codes, ALA and IFLA forms, open access agreements, and purchase on demand plans." -- Publisher's description.